2008
DOI: 10.1155/2008/692573
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclodextrin Glycosyltransferase of Paenibacillus pabuli US132 Strain: Molecular Characterization and Overproduction of the Recombinant Enzyme

Abstract: The gene encoding the cyclodextrin glycosyltransferase (CGTase) of Paenibacillus pabuli US132, previously described as efficient antistaling agent and good candidate for cyclodextrins production, was cloned, sequenced, and expressed in Escherichia coli. Sequence analysis showed that the mature enzyme (684 amino acids) was preceded by a signal peptide of 34 residues. The enzyme exhibited the highest identity (94%) to the β-CGTase of Bacillus circulans no. 8. The production of the recombinant CGTase, as active f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The monitoring of the CGTase activity in the cell crude extract, periplasmic fraction and the supernatant, showed a clearly detectable activity of 2 U/mL (95%) in the extracellular juice of DH5α/pAD23 strain against of only 0.08 U/mL (1.5%) and 0.2 U/mL of culture (3.5%) in the cytoplasmic and periplasmic frac- tions, respectively. In contrast, in the case of the CGTase US132 with its natural signal peptide, the CGTase activity was mainly periplasmic evaluated to be 1 U/mL (98%), while no detected activity was found in the supernatant and only 2% in the cytoplasmic fraction, as already reported by Jemli et al (2008). Thus, enzyme localization showed that the enzyme was efficiently expressed and secreted into the supernatant in catalytically active conformation with specific activity of about 400 U/mg.…”
Section: Extracellular Secretion Of Cgtase Using the Ssamysupporting
confidence: 51%
See 2 more Smart Citations
“…The monitoring of the CGTase activity in the cell crude extract, periplasmic fraction and the supernatant, showed a clearly detectable activity of 2 U/mL (95%) in the extracellular juice of DH5α/pAD23 strain against of only 0.08 U/mL (1.5%) and 0.2 U/mL of culture (3.5%) in the cytoplasmic and periplasmic frac- tions, respectively. In contrast, in the case of the CGTase US132 with its natural signal peptide, the CGTase activity was mainly periplasmic evaluated to be 1 U/mL (98%), while no detected activity was found in the supernatant and only 2% in the cytoplasmic fraction, as already reported by Jemli et al (2008). Thus, enzyme localization showed that the enzyme was efficiently expressed and secreted into the supernatant in catalytically active conformation with specific activity of about 400 U/mg.…”
Section: Extracellular Secretion Of Cgtase Using the Ssamysupporting
confidence: 51%
“…After centrifugation (7,500×g, 10 min), the supernatant was used as crude enzyme solution for assaying enzyme activity. The periplasmic and cytoplasmic proteins were prepared as described by Jemli et al (2008).…”
Section: Preparation Of Crude Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid pSJ8 carrying the wild-type US132 cgtase gene was previously described (Jemli et al 2008). The pCR2.1 vector (Invitrogen) was used for the cloning of mutated US132 cgtase genes.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…In previous works, the conventional CGTase from Paenibacillus pabuli US132 (US132 CGTase) was characterized, cloned and overexpressed (Jemli et al 2008;Zouari Ayadi et al 2011). In addition, the enzyme has been reported as a potential good candidate for application as an anti-staling agent particularly because of its action on bread firmness (Jemli et al 2007).…”
Section: Introductionmentioning
confidence: 99%